1 Public Records of the Colony of Connecticut 79 (J. Hammond Trumbull ed., 1850) (enacted 1644) - (:unkn) unknown (My University, 1665)
Prohibited the repairing, selling, and giving "any Indian" a gun or ammunition, punishable by fine.
Keywords: TRANSFER - DANGEROUS PERSONS